Socio-Religious Movement of Religious Affiliated Student Organizations After Social Conflict in Ambon - Yance Z. Rumahuru (Al-Albab, 2016)
This article examines student social movements with a focus of student activities in extra-campus organizations, especially the Islamic Students Association (HMI) and the Indonesian Christian Students’ Movement (GMKI) at the campus of the Pattimura University, State College of Islamic Studies Of Ambon and the State College of Protestant Christian Studies Ambon, which aims to describe forms of student social movements in responding to social issues and development in the city of Ambon and Maluku after the conflict. The data of this study were collected using a qualitative method approach through observation, interviews and document study. Therefore, this study is qualitative, the data were analyzed qualitatively and presented descriptively. This study found that first, cadres or members of HMI and GMKI always strive to master public spaces on campus through the distribution of their cadres to occupy strategic positions in the executive bodies or the student senate, even the seniors who have become lecturers in structural positions on campus, which in turn can affect campus policies. Second, the activities in the movement of HMI and GMKI have similarities in terms of responding to social issues, by paying attention to a few aspects including socio-religious issues, local political issues and post-conflict community development.